INTERNAL CONTROL AND RISK MANAGEMENT ANALYSIS IN PROPERTY BROKERAGE COMPANIES - Handoko, Jessica; Melati, Indah (LPPM STIE Muhammadiah Bandung, 2023)
This study aims to analyze and provide recommendations for increasing the effectiveness of internal control and risk management at PT XYZ. PT XYZ is a medium-sized company engaged in property brokerage. This case study describes the implementation of internal control and risk management at PT XYZ with an analysis based on COSO internal control and COSO ERM. This research uses a qualitative descriptive method with interviews and direct observation as a data collection technique. With this research, it is expected to provide suggestions for improvements related to internal control and risk management.